Management of Sensor-Related Data Based on Virtual TEDS in Sensing RFID System. (19th March 2015) - Luo, Wuming; Bolic, Miodrag; Wang, Jing; Qian, Xin
Abstract : Integration of multiple sensors into active radio frequency identification (RFID) system is a technology trend. Currently, sensing RFID (SRFID) systems face a number of challenges including description of characteristics of nonsmart sensors, management of sensor-related data, and operational mechanism of sensor sampling. Based on transducer electronic data sheet (TEDS), this paper presents a virtual description method of nonsmart sensors integrated into the active RFID tag. The objective is to improve interoperability and compatibility of the sensing RFID system with off-the-shelf active RFID readers or novel sensing RFID open-loop systems in the future. This paper also proposes a data table storage mode for management of sensor-related data, in the system based on virtual TEDS. The paper analyses the operational mechanism and procedure of the sensor-sampling system that is equipped with these two proposed techniques. Several experiments were carried out with a newly developed container supply chain monitoring application system based on SRFID to examine the performance of the system.